Analysis of the Strength of Development Agencies in Village Development Planning - Umar Nain (Universitas Negeri Makassar, 2019)
The government in realizing village development cannot be separated from the role of mature planning. In this study aims to analyze the strength of the development agency in village development planning. Respondents in this study were 103 respondents consisting of farmers = 65 people, breeders = 21 people, grocery merchants = 13 people, and civil servants = 4 people. The data analysis technique used a quantitative approach using multiple regression to see the relationship between independent variables and the dependent variable. Independent variables are the suprades government, village communities, market participants and the dependent variable is village development planning. The quantitative data contained in each variable will be processed using the application SPSS for windows 20.0. The results of the study indicate that the strength of development agencies contributes to village development planning. This can be seen from the Market Actors, the Supradesa Government and the Village Community.